The Application of Quizizz as an Interactive Learning Medium to Enhance Student Learning Engagement - Hijrat, Kasim; Asiyah, Siti (At- Ta'lim : Jurnal Pendidikan, 2025)
Student engagement plays a key role in the success of the learning process, as it directly affects students’ understanding, motivation, and ability to think critically. To encourage greater participation, Quizizz a game-based learning platform has shown strong potential. This study sought to enhance the engagement of fifth-grade students at SDN 3 Lamahala by integrating interactive learning activities through Quizizz. The research focused on three main indicators: students’ ability to ask questions, attentiveness during the teacher’s explanations, and independence in completing assignments. Using a Classroom Action Research (CAR) approach, the study was conducted over two cycles, each involving four stages: planning, implementation, observation, and reflection. The results of the study showed a significant increase in student learning activity. In the pre-cycle stage, the activity level was only 24%. This figure increased to 52% at the end of cycle I and reached its peak at 80% in cycle II. Thus, it can be concluded that the use of the Quizizz application is effective in increasing student learning activity and creating a more enjoyable, interactive, and participatory learning atmosphere.